Studi Eksperimental Sifat Fisik dan Mekanik Batu Gamping - Bagas Aryaseta; Primasari Cahya Wardhani; Siti Zainab (KERN, 2022)
An experiment has been carried out on Limestone specimens to determine the physical and mechanical properties. In this experiment, a non-destructive method was used, namely by using an ultrasonic device and an oscilloscope. As a result, ultrasonic devices and oscilloscopes are able to measure the velocity of the P-wave very well. In addition, this research also includes measuring the internal physical properties of rocks such as porosity and density. Then, the mechanical parameters of Limestone are calculated based on the existing theory. Several important parameter values obtained such as Compressional Wave Modulus (M), Bulk Modulus (k), and Shear Modulus (μ) are 58.72 GPa, 19.57 GPa, and 29.36 GPa, respectively.